Boosting Students' Vocabulary Mastery through YouTube: A Game-Changer in Learning - Rini, Yulan Puspita; Kholid, Mohammad Fikri Nugraha; Lizana, Clarissa (IJLHE: International Journal of Language, Humanities, and Education, 2024)
This study investigated the impact of YouTube as a learning medium on vocabulary mastery among seventh-grade students at SMP Negeri 33 Bandar Lampung during the 2024/2025 academic year. While YouTube is primarily known as an entertainment platform, it can also serve as an effective tool for learning, particularly in enhancing vocabulary. Employing a quantitative pre-experimental design with a one-group pretest-posttest approach, the research involved 35 students selected from a population of 173 across five classes. The study utilized descriptive text materials, with data collected through pretests and posttests administered before and after using YouTube videos as learning aids. Pretest and posttest scores were analyzed using paired sample t-tests via SPSS 16. The analysis revealed a significant result (Sig. = 0.000 < α = 0.05), confirming that YouTube had a significant effect on students’ vocabulary mastery. The findings imply that incorporating YouTube as a teaching tool can enhance language learning outcomes and provide an engaging platform for vocabulary development